Analisis Kesuksesan Sistem Pembelajaran E-learning di Sekolah Menengah Atas Kabupaten Jember Dengan Menggunakan Metode Information System Success Model (ISSM) (Studi Kasus : MAN 1 Jember) - Kelvin Adha Firullah (Fakultas Ilmu Komputer, 2023)
E-learning is a fairly new learning tool used by the MAN 1 Jember school. In this school, E-learning is used for teaching and learning activities with the aim of efficient time and space. The success of E-learning requires evaluation for improvement and development. The aim of this research is to find out the factors that can influence the success of MAN 1 Jember E-learning and to find out recommendations that can be given to the success of the MAN 1 Jember E-learning system. The measurement method in this research uses the Information System Success Model (ISSM) developed by DeLone & McLean. Data collection was carried out by distributing closed questionnaires to a research sample of 303 respondents. Instrument tests carried out include convergent and discriminant validity tests as well as reliability tests. For data analysis, model fit tests and hypothesis tests were carried out. This research uses SmartPLS software as a tool for analysis. The variables used in this research are Information Quality (IQ), System Quality (SQ), Service Quality (SEQ), interest in using (IU), User Satisfaction (US), and Net Benefit (NB). Of the 9 hypotheses prepared, 3 of them were rejected, namely the influence of IQ on IU had an insignificant relationship, because the P-Value value (0.327) was greater than the significance level usually used, namely 0.05. The relationship between the SEQ and IU variables is not significant, because the P-Value value (0.821) is greater than 0.05. The relationship between the SQ and IU variables is not significant, although the P-Value (0.085) is quite close to the significance level.
Reupload file repositori 30 januari 2026_Kurnadi/Mita
Keywords: DeLone & McLean; SmartPLS